"I sit to sleep"—Spirometry as a clue to diagnosis. Issue 4 (17th December 2015) - Yaacoby‐Bianu, Karin; Shaul, Ron; Ilivitzki, Anat; Bentur, Lea
Summary: A 15‐year‐old patient presented with a 4‐month history of choking while sleeping that necessitated sleeping in a sitting position. Flow‐volume curve demonstrating fixed upper airway obstruction led to further workup and to the diagnosis of childhood achalasia as a cause of unusual symptoms and fixed upper airway obstruction.Pediatr Pulmonol. 2016;51:E13–E15 . © 2015 Wiley Periodicals, Inc.